Diversity and source-tracking of spoilage molds in bakery products using MALDI-TOF MS and molecular approaches - Nolwenn Rolland; Jérôme Mounier; Mélanie Cadoret; Victoria Girard; Guillaume Perrin; Sylvie Treguer; Océane Cloarec; Nicolas Nguyen Van Long; Lionel Fiabane; Franck Deniel; Valérie Vasseur; Jean-Luc Jany (International Journal of Food Microbiology, 2026)

Blood flow restriction exacerbates muscle deoxygenation and fatigue during sport climbing specific finger flexors resistance training - Titouan P. Perrin; Hugo Randy; Xavier Hugues; Nicolas Tourette; Marie Coudurier; Michel Guinot; Violaine Cahouet; Franck Quaine; Stéphane Doutreleau; Hugo A. Kerherve; Mathieu Marillier; Julien V. Brugniaux (European Journal of Applied Physiology, 2026)

Nitrogen fixation in Arctic lichens and mosses: A survey across circumpolar subzones - Perrin Hagge; Elizabeth King-Doonan; François Lutzoni; Jolanta Miadlikowska; Blanka Aguero; Hannah Whitby; Charles Umbanhowar; Claudia Colesie; A. Elizabeth Arnold; Eric Yitong; Nicolas Cassar (Science of The Total Environment, 2025)

Range expansion and reconnection of historical populations in the Eurasian otter (Lutra lutra) in France: Insights from heterogeneous data and integrated species distribution modelling - Simon Lacombe; Sébastien Devillard; Cécile Kauffmann; Mélanie Aznar; Ondine Dupuis; Christine Fournier-Chambrillon; Estelle Isère-Laoué; Camille Fraissard; Nicolas Fuento; Tiphaine Heugas; Alexandre Martin; Magali Perrin; et al. (Biological Conservation, 2025)

Citizen science approach for genetic species identification in a local French seafood speciality - Babett Günther; Nicolas Bierne; Philippe Borsa; Cécile Perrin; Olivier Ripoll; Fanny Darbois; Sophie Arnaud-Haond (International Journal of Gastronomy and Food Science, 2024)

Differential influence of temperature on the toxicity of three insecticides against the codling moth Cydia pomonella (L.) and two natural enemies - Marie Perrin; Nicolas Borowiec; Marcel Thaon; Myriam Siegwart; Thomas Delattre; Joffrey Moiroux (Journal of Pest Science, 2024)

Identification of ancestral sex chromosomes in the frog Glandirana rugosa bearing XX‐XY and ZZ‐ZW sex‐determining systems - Ikuo Miura; Foyez Shams; Daniel Lee Jeffries; Yukako Katsura; Shuuji Mawaribuchi; Nicolas Perrin; Michihiko Ito; Mitsuaki Ogata; Tariq Ezaz (Molecular Ecology, 2022)
Sex chromosomes constantly exist in a dynamic state of evolution: rapid turnover and change of heterogametic sex during homomorphic state, and often stepping out to a heteromorphic state followed by chromosomal decaying. However, the forces driving these different trajectories of sex chromosome evolution are still unclear. The Japanese frog Glandirana rugosa is one taxon well suited to the study on these driving forces. The species has two different heteromorphic sex chromosome systems, XX‐XY and ZZ‐ZW, which are separated in different geographic populations. Both XX‐XY and ZZ‐ZW sex chromosomes are represented by chromosome 7 (2n = 26). Phylogenetically, these two systems arose via hybridization between two ancestral lineages of West Japan and East Japan populations, of which sex chromosomes are homomorphic in both sexes and to date have not yet been identified. Identification of the sex chromosomes will give us important insight into the mechanisms of sex chromosome evolution in this species. Here, we used a high‐throughput genomic approach to identify the homomorphic XX‐XY sex chromosomes in both ancestral populations. Sex‐linked DNA markers of West Japan were aligned to chromosome 1, whereas those of East Japan were aligned to chromosome 3. These results reveal that at least two turnovers across three different sex chromosomes 1, 3 and 7 occurred during evolution of this species. This finding raises the possibility that cohabitation of the two different sex chromosomes from ancestral lineages induced turnover to another new one in their hybrids, involving transition of heterogametic sex and evolution from homomorphy to heteromorphy.

Are glacial refugia hotspots of speciation and cytonuclear discordances? Answers from the genomic phylogeography of Spanish common frogs - Christophe Dufresnes; Alfredo G. Nicieza; Spartak N. Litvinchuk; Nicolas Rodrigues; Daniel L. Jeffries; Miguel Vences; Nicolas Perrin; Íñigo Martínez‐Solano (Molecular Ecology, 2020)
Subdivided Pleistocene glacial refugia, best known as “refugia within refugia”, provided opportunities for diverging populations to evolve into incipient species and/or to hybridize and merge following range shifts tracking the climatic fluctuations, potentially promoting extensive cytonuclear discordances and “ghost” mtDNA lineages. Here, we tested which of these opposing evolutionary outcomes prevails in northern Iberian areas hosting multiple historical refugia of common frogs ( Rana cf. temporaria ), based on a genomic phylogeography approach (mtDNA barcoding and RAD‐sequencing). We found evidence for both incipient speciation events and massive cytonuclear discordances. On the one hand, populations from northwestern Spain (Galicia and Asturias, assigned to the regional endemic R. parvipalmata ), are deeply‐diverged at mitochondrial and nuclear genomes (~4 My of independent evolution), and barely admix with northeastern populations (assigned to R. temporaria sensu stricto) across a narrow hybrid zone (~25 km) located in the Cantabrian Mountains, suggesting that they represent distinct species. On the other hand, the most divergent mtDNA clade, widespread in Cantabria and the Basque country, shares its nuclear genome with other R. temporaria s. s. lineages. Patterns of population expansions and isolation‐by‐distance among these populations are consistent with past mitochondrial capture and/or drift in generating and maintaining this ghost mitochondrial lineage. This remarkable case study emphasizes the complex evolutionary history that shaped the present genetic diversity of refugial populations, and stresses the need to revisit their phylogeography by genomic approaches, in order to make informed taxonomic inferences.

Phylogeography of a cryptic speciation continuum in Eurasian spadefoot toads ( Pelobates ) - Christophe Dufresnes; Ilias Strachinis; Nataliia Suriadna; Galyna Mykytynets; Dan Cogălniceanu; Paul Székely; Tanja Vukov; Jan W. Arntzen; Ben Wielstra; Petros Lymberakis; Eli Geffen; Sarig Gafny; et al. (Molecular Ecology, 2019)
Cryptic phylogeographic diversifications provide unique models to examine the role of phylogenetic divergence on the evolution of reproductive isolation, without extrinsic factors such as ecological and behavioural differentiation. Yet, to date very few comparative studies have been attempted within such radiations. Here, we characterize a new speciation continuum in a group of widespread Eurasian amphibians, the Pelobates spadefoot toads, by conducting multilocus (restriction site associated DNA sequencing and mitochondrial DNA) phylogenetic, phylogeographic and hybrid zone analyses. Within the P. syriacus complex, we discovered species‐level cryptic divergences (>5 million years ago [My]) between populations distributed in the Near‐East (hereafter P. syriacus sensu stricto [ s.s .]) and southeastern Europe (hereafter P. balcanicus ), each featuring deep intraspecific lineages. Altogether, we could scale hybridizability to divergence time along six different stages, spanning from sympatry without gene flow ( P. fuscus and P. balcanicus , >10 My), parapatry with highly restricted hybridization ( P. balcanicus and P. syriacus s.s ., >5 My), narrow hybrid zones (~15 km) consistent with partial reproductive isolation ( P. fuscus and P. vespertinus , ~3 My), to extensive admixture between Pleistocene and refugial lineages (≤2 My). This full spectrum empirically supports a gradual build up of reproductive barriers through time, reversible up until a threshold that we estimate at ~3 My. Hence, cryptic phylogeographic lineages may fade away or become reproductively isolated species simply depending on the time they persist in allopatry, and without definite ecomorphological divergence.

A reciprocal translocation radically reshapes sex‐linked inheritance in the common frog - Melissa A. Toups; Nicolas Rodrigues; Nicolas Perrin; Mark Kirkpatrick (Molecular Ecology, 2019)
X and Y chromosomes can diverge when rearrangements block recombination between them. Here we present the first genomic view of a reciprocal translocation that causes two physically unconnected pairs of chromosomes to be coinherited as sex chromosomes. In a population of the common frog ( Rana temporaria ), both pairs of X and Y chromosomes show extensive sequence differentiation, but not degeneration of the Y chromosomes. A new method based on gene trees shows both chromosomes are sex‐linked. Furthermore, the gene trees from the two Y chromosomes have identical topologies, showing they have been coinherited since the reciprocal translocation occurred. Reciprocal translocations can thus reshape sex linkage on a much greater scale compared with inversions, the type of rearrangement that is much better known in sex chromosome evolution, and they can greatly amplify the power of sexually antagonistic selection to drive genomic rearrangement. Two more populations show evidence of other rearrangements, suggesting that this species has unprecedented structural polymorphism in its sex chromosomes.

Dmrt1 polymorphism and sex‐chromosome differentiation in Rana temporaria - Nicolas Rodrigues; Tania Studer; Christophe Dufresnes; Wen‐Juan Ma; Paris Veltsos; Nicolas Perrin (Molecular Ecology, 2017)
Sex‐determination mechanisms vary both within and among populations of common frogs, opening opportunities to investigate the molecular pathways and ultimate causes shaping their evolution. We investigated the association between sex‐chromosome differentiation (as assayed from microsatellites) and polymorphism at the candidate sex‐determining gene Dmrt1 in two Alpine populations. Both populations harboured a diversity of X‐linked and Y‐linked Dmrt1 haplotypes. Some males had fixed male‐specific alleles at all markers (“differentiated” Y chromosomes), others only at Dmrt1 (“proto‐” Y chromosomes), while still others were genetically indistinguishable from females (undifferentiated X chromosomes). Besides these XX males, we also found rare XY females. The several Dmrt1 Y haplotypes differed in the probability of association with a differentiated Y chromosome, which we interpret as a result of differences in the masculinizing effects of alleles at the sex‐determining locus. From our results, the polymorphism in sex‐chromosome differentiation and its association with Dmrt1 , previously inferred from Swedish populations, are not just idiosyncratic features of peripheral populations, but also characterize highly diverged populations in the central range. This implies that an apparently unstable pattern has been maintained over long evolutionary times.

Cryptic invasion of Italian pool frogs (Pelophylax bergeri) across Western Europe unraveled by multilocus phylogeography - Christophe Dufresnes; Lionel Di Santo; Julien Leuenberger; Johan Schuerch; Glib Mazepa; Nathalie Grandjean; Daniele Canestrelli; Nicolas Perrin; Sylvain Dubey (Biological Invasions, 2017)

Hydrological response characteristics of Mediterranean catchments at different time scales: a meta-analysis - Mohammad Merheb; Roger Moussa; Chadi Abdallah; François Colin; Charles Perrin; Nicolas Baghdadi (Hydrological Sciences Journal, 2016)

Evolutionary melting pots: a biodiversity hotspot shaped by ring diversifications around the Black Sea in the Eastern tree frog ( Hyla orientalis ) - Christophe Dufresnes; Spartak N. Litvinchuk; Julien Leuenberger; Karim Ghali; Oleksandr Zinenko; Matthias Stöck; Nicolas Perrin (Molecular Ecology, 2016)
Hotspots of intraspecific genetic diversity, which are of primary importance for the conservation of species, have been associated with glacial refugia, that is areas where species survived the Quaternary climatic oscillations. However, the proximate mechanisms generating these hotspots remain an open issue. Hotspots may reflect the long‐term persistence of large refugial populations; alternatively, they may result from allopatric differentiation between small and isolated populations, that later admixed. Here, we test these two scenarios in a widely distributed species of tree frog, Hyla orientalis , which inhabits Asia Minor and southeastern Europe. We apply a fine‐scale phylogeographic survey, combining fast‐evolving mitochondrial and nuclear markers, with a dense sampling throughout the range, as well as ecological niche modelling, to understand what shaped the genetic variation of this species. We documented an important diversity centre around the Black Sea, composed of multiple allopatric and/or parapatric diversifications, likely driven by a combination of Pleistocene climatic fluctuations and complex regional topography. Remarkably, this diversification forms a ring around the Black Sea, from the Caucasus through Anatolia and eastern Europe, with terminal forms coming into contact and partially admixing in Crimea. Our results support the view that glacial refugia generate rather than host genetic diversity and can also function as evolutionary melting pots of biodiversity. Moreover, we report a new case of ring diversification, triggered by a large, yet cohesive dispersal barrier, a very rare situation in nature. Finally, we emphasize the Black Sea region as an important centre of intraspecific diversity in the Palearctic with implications for conservation.

Massive genetic introgression in threatened northern crested newts (Triturus cristatus) by an invasive congener (T. carnifex) in Western Switzerland - Christophe Dufresnes; Jérôme Pellet; Sandra Bettinelli-Riccardi; Jacques Thiébaud; Nicolas Perrin; Luca Fumagalli (Conservation Genetics, 2016)

Introgressive hybridization of threatened European tree frogs (Hyla arborea) by introduced H. intermedia in Western Switzerland - Christophe Dufresnes; Sylvain Dubey; Karim Ghali; Daniele Canestrelli; Nicolas Perrin (Conservation Genetics, 2015)

Graphical tools based on Turc-Budyko plots to detect changes in catchment behaviour - Laurent Coron; Vazken Andréassian; Charles Perrin; Nicolas Le Moine (Hydrological Sciences Journal, 2015)

Effect of biogeographic history on population vulnerability in European amphibians - Christophe Dufresnes; Nicolas Perrin (Conservation Biology, 2015)
The genetic diversity of populations, which contributes greatly to their adaptive potential, is negatively affected by anthropogenic habitat fragmentation and destruction. However, continental‐scale losses of genetic diversity also resulted from the population expansions that followed the end of the last glaciation, an element that is rarely considered in a conservation context. We addressed this issue in a meta‐analysis in which we compared the spatial patterns of vulnerability of 18 widespread European amphibians in light of phylogeographic histories (glacial refugia and postglacial routes) and anthropogenic disturbances. Conservation statuses significantly worsened with distances from refugia, particularly in the context of industrial agriculture; human population density also had a negative effect. These findings suggest that features associated with the loss of genetic diversity in post‐glacial amphibian populations (such as enhanced fixation load or depressed adaptive potential) may increase their susceptibility to current threats (e.g., habitat fragmentation and pesticide use). We propose that the phylogeographic status of populations (i.e., refugial vs. post‐glacial) should be considered in conservation assessments for regional and national red lists.

Are invasive marsh frogs (Pelophylax ridibundus) replacing the native P. lessonae/P. esculentus hybridogenetic complex in Western Europe? Genetic evidence from a field study - Julien Leuenberger; Antoine Gander; Benedikt R. Schmidt; Nicolas Perrin (Conservation Genetics, 2014)

Geographic variation in sex‐chromosome differentiation in the common frog ( R ana temporaria ) - Nicolas Rodrigues; Juha Merilä; Cécile Patrelle; Nicolas Perrin (Molecular Ecology, 2014)
In sharp contrast with birds and mammals, sex‐determination systems in ectothermic vertebrates are often highly dynamic and sometimes multifactorial. Both environmental and genetic effects have been documented in common frogs ( R ana temporaria ). One genetic linkage group, mapping to the largest pair of chromosomes and harbouring the candidate sex‐determining gene Dmrt1 , associates with sex in several populations throughout E urope, but association varies both within and among populations. Here, we show that sex association at this linkage group differs among populations along a 1500‐km transect across Sweden. Genetic differentiation between sexes is strongest ( F ST = 0.152) in a northern‐boreal population, where male‐specific alleles and heterozygote excesses ( F IS = −0.418 in males, +0.025 in females) testify to a male‐heterogametic system and lack of X ‐ Y recombination. In the southernmost population (nemoral climate), in contrast, sexes share the same alleles at the same frequencies ( F ST = 0.007 between sexes), suggesting unrestricted recombination. Other populations show intermediate levels of sex differentiation, with males falling in two categories: some cluster with females, while others display male‐specific Y haplotypes. This polymorphism may result from differences between populations in the patterns of X ‐ Y recombination, co‐option of an alternative sex‐chromosome pair, or a mixed sex‐determination system where maleness is controlled either by genes or by environment depending on populations or families. We propose approaches to test among these alternative models, to disentangle the effects of climate and phylogeography on the latitudinal trend, and to sort out how this polymorphism relates to the ‘sexual races’ described in common frogs in the 1930s.

Conservation phylogeography: does historical diversity contribute to regional vulnerability in E uropean tree frogs ( H yla arborea )? - Christophe Dufresnes; Jérôme Wassef; Karim Ghali; Alan Brelsford; Matthias Stöck; Petros Lymberakis; Jelka Crnobrnja‐Isailovic; Nicolas Perrin (Molecular Ecology, 2013)
Documenting and preserving the genetic diversity of populations, which conditions their long‐term survival, have become a major issue in conservation biology. The loss of diversity often documented in declining populations is usually assumed to result from human disturbances; however, historical biogeographic events, otherwise known to strongly impact diversity, are rarely considered in this context. We apply a multilocus phylogeographic study to investigate the late‐Quaternary history of a tree frog ( H yla arborea ) with declining populations in the northern and western part of its distribution range. Mitochondrial and nuclear polymorphisms reveal high genetic diversity in the Balkan Peninsula, with a spatial structure moulded by the last glaciations. While two of the main refugial lineages remained limited to the Balkans (Adriatic coast, southern Balkans), a third one expanded to recolonize Northern and Western Europe, loosing much of its diversity in the process. Our findings show that mobile and a priori homogeneous taxa may also display substructure within glacial refugia (‘refugia within refugia’) and emphasize the importance of the Balkans as a major European biodiversity centre. Moreover, the distribution of diversity roughly coincides with regional conservation situations, consistent with the idea that historically impoverished genetic diversity may interact with anthropogenic disturbances, and increase the vulnerability of populations. Phylogeographic models seem important to fully appreciate the risks of local declines and inform conservation strategies.

Development and cross-amplification of thirty microsatellite loci in five diploid and polyploid Central Asian species of Palearctic green toads (Bufo viridis subgroup) - Caroline Betto-Colliard; Roberto Sermier; Nicolas Perrin; Matthias Stöck (Conservation Genetics Resources, 2013)

Social systems: demographic and genetic issues - NICOLAS PERRIN; ERIC J. PETIT; NELLY MENARD (Molecular Ecology, 2012)

Polymorphism at a Sex-Linked Transcription Cofactor in European Tree Frogs (Hyla arborea): Sex-Antagonistic Selection or Neutral Processes? - Christophe Dufresnes; Emilien Luquet; Sandrine Plenet; Matthias Stöck; Nicolas Perrin (Evolutionary Biology, 2011)

Thirteen polymorphic microsatellite markers for the European green toad Bufo viridis viridis, a declining amphibian species - Christophe Dufresnes; Caroline Betto-Colliard; Nicolas Perrin; Matthias Stöck (Conservation Genetics Resources, 2011)

Genetic Bottlenecks Driven by Population Disconnection - THOMAS BROQUET; SONIA ANGELONE; JULIE JAQUIERY; PIERRE JOLY; JEAN‐PAUL LENA; THIERRY LENGAGNE; SANDRINE PLENET; EMILIEN LUQUET; NICOLAS PERRIN (Conservation Biology, 2010)
Connectivity among populations plays a crucial role in maintaining genetic variation at a local scale, especially in small populations affected strongly by genetic drift. The negative consequences of population disconnection on allelic richness and gene diversity (heterozygosity) are well recognized and empirically established. It is not well recognized, however, that a sudden drop in local effective population size induced by such disconnection produces a temporary disequilibrium in allelic frequency distributions that is akin to the genetic signature of a demographic bottleneck. To document this effect, we used individual‐based simulations and empirical data on allelic richness and gene diversity in six pairs of isolated versus well‐connected (core) populations of European tree frogs. In our simulations, population disconnection depressed allelic richness more than heterozygosity and thus resulted in a temporary excess in gene diversity relative to mutation drift equilibrium (i.e., signature of a genetic bottleneck). We observed a similar excess in gene diversity in isolated populations of tree frogs. Our results show that population disconnection can create a genetic bottleneck in the absence of demographic collapse.

Flexible social organization and high incidence of drifting in the sweat bee, Halictus scabiosae - YUKO ULRICH; NICOLAS PERRIN; MICHEL CHAPUISAT (Molecular Ecology, 2009)
The very diverse social systems of sweat bees make them interesting models to study social evolution. Here we focus on the dispersal behaviour and social organization of Halictus scabiosae , a common yet poorly known species of Europe. By combining field observations and genetic data, we show that females have multiple reproductive strategies, which generates a large diversity in the social structure of nests. A detailed microsatellite analysis of 60 nests revealed that 55% of the nests contained the offspring of a single female, whereas the rest had more complex social structures, with three clear cases of multiple females reproducing in the same nest and frequent occurrence of unrelated individuals. Drifting among nests was surprisingly common, as 16% of the 122 nests in the overall sample and 44% of the nests with complex social structure contained females that had genotypes consistent with being full‐sisters of females sampled in other nests of the population. Drifters originated from nests with an above‐average productivity and were unrelated to their nestmates, suggesting that drifting might be a strategy to avoid competition among related females. The sex‐specific comparison of genetic differentiation indicated that dispersal was male‐biased, which would reinforce local resource competition among females. The pattern of genetic differentiation among populations was consistent with a dynamic process of patch colonization and extinction, as expected from the unstable, anthropogenic habitat of this species. Overall, our data show that H. scabiosae varies greatly in dispersal behaviour and social organization. The surprisingly high frequency of drifters echoes recent findings in wasps and bees, calling for further investigation of the adaptive basis of drifting in the social insects.

Inferring recent migration rates from individual genotypes - THOMAS BROQUET; JONATHAN YEARSLEY; ALEXANDRE H. HIRZEL; JÉRÔME GOUDET; NICOLAS PERRIN (Molecular Ecology, 2009)
We present a novel and straightforward method for estimating recent migration rates between discrete populations using multilocus genotype data. The approach builds upon a two‐step sampling design, where individual genotypes are sampled before and after dispersal. We develop a model that estimates all pairwise backwards migration rates ( m ij , the probability that an individual sampled in population i is a migrant from population j ) between a set of populations. The method is validated with simulated data and compared with the methods of BayesAss and Structure. First, we use data for an island model and then we consider more realistic data simulations for a metapopulation of the greater white‐toothed shrew ( Crocidura russula ). We show that the precision and bias of estimates primarily depend upon the proportion of individuals sampled in each population. Weak sampling designs may particularly affect the quality of the coverage provided by 95% highest posterior density intervals. We further show that it is relatively insensitive to the number of loci sampled and the overall strength of genetic structure. The method can easily be extended and makes fewer assumptions about the underlying demographic and genetic processes than currently available methods. It allows backwards migration rates to be estimated across a wide range of realistic conditions.

Communally breeding Bechstein's bats have a stable social system that is independent from the postglacial history and location of the populations - GERALD KERTH; BOYAN PETROV; ANDREJ CONTI; DANIJELA ANASTASOV; MANFRED WEISHAAR; SUREN GAZARYAN; JULIE JAQUIÉRY; BARBARA KÖNIG; NICOLAS PERRIN; NADIA BRUYNDONCKX (Molecular Ecology, 2008)
Investigating macro‐geographical genetic structures of animal populations is crucial to reconstruct population histories and to identify significant units for conservation. This approach may also provide information about the intraspecific flexibility of social systems. We investigated the history and current structure of a large number of populations in the communally breeding Bechstein's bat ( Myotis bechsteinii ). Our aim was to understand which factors shape the species’ social system over a large ecological and geographical range. Using sequence data from one coding and one noncoding mitochondrial DNA region, we identified the Balkan Peninsula as the main and probably only glacial refugium of the species in Europe. Sequence data also suggest the presence of a cryptic taxon in the Caucasus and Anatolia. In a second step, we used seven autosomal and two mitochondrial microsatellite loci to compare population structures inside and outside of the Balkan glacial refugium. Central European and Balkan populations both were more strongly differentiated for mitochondrial DNA than for nuclear DNA, had higher genetic diversities and lower levels of relatedness at swarming (mating) sites than in maternity (breeding) colonies, and showed more differentiation between colonies than between swarming sites. All these suggest that populations are shaped by strong female philopatry, male dispersal, and outbreeding throughout their European range. We conclude that Bechstein's bats have a stable social system that is independent from the postglacial history and location of the populations. Our findings have implications for the understanding of the benefits of sociality in female Bechstein's bats and for the conservation of this endangered species.

Projecting future N 2 O emissions from agricultural soils in Belgium - CAROLINE ROELANDT; NICOLAS DENDONCKER; MARK ROUNSEVELL; DOMINIQUE PERRIN; BAS VAN WESEMAEL (Global Change Biology, 2007)
This study analyses the spatial and temporal variability of N 2 O emissions from the agricultural soils of Belgium. Annual N 2 O emission rates are estimated with two statistical models, MCROPS and MGRASS, which take account of the impact of changes in land use, climate, and nitrogen‐fertilization rate. The models are used to simulate the temporal trend of N 2 O emissions between 1990 and 2050 for a 10′ latitude and longitude grid. The results are also aggregated to the regional and national scale to facilitate comparison with other studies and national inventories. Changes in climate and land use are derived from the quantitative scenarios developed by the ATEAM project based on the Intergovernmental Panel on Climate Change‐Special Report on Emissions Scenarios (IPCC‐SRES) storylines. The average N 2 O flux for Belgium was estimated to be 8.6 × 10 6 kg N 2 O‐N yr −1 (STD = 2.1 × 10 6 kg N 2 O‐N yr −1 ) for the period 1990–2000. Fluxes estimated for a single year (1996) give a reasonable agreement with published results at the national and regional scales for the same year. The scenario‐based simulations of future N 2 O emissions show the strong influence of land‐use change. The scenarios A1FI, B1 and B2 produce similar results between 2001 and 2050 with a national emission rate in 2050 of 11.9 × 10 6 kg N 2 O‐N yr −1 . The A2 scenario, however, is very sensitive to the reduction in agricultural land areas (−14% compared with the 1990 baseline), which results in a reduced emission rate in 2050 of 8.3 × 10 6 kg N 2 O‐N yr −1 . Neither the climatic change scenarios nor the reduction in nitrogen fertilization rate could explain these results leading to the conclusion that N 2 O emissions from Belgian agricultural soils will be more markedly affected by changes in agricultural land areas.

Density, climate and varying return points: an analysis of long-term population fluctuations in the threatened European tree frog - Jérôme Pellet; Benedikt R. Schmidt; Fabien Fivaz; Nicolas Perrin; Kurt Grossenbacher (Oecologia, 2006)

Viability and Management of an Endangered Capercaillie (Tetrao urogallus) Metapopulation in the Jura Mountains, Western Switzerland - Sébastien Sachot; Nicolas Perrin; Cornelis Neet (Biodiversity and Conservation, 2006)

Nonshivering thermogenesis capacity associated to mitochondrial DNA haplotypes and gender in the greater white‐toothed shrew, Crocidura russula - PIERRE FONTANILLAS; ALINE DÉPRAZ; MAUD S. GIORGI; NICOLAS PERRIN (Molecular Ecology, 2005)
A selection gradient was recently suggested as one possible cause for a clinal distribution of mitochondrial DNA (mtDNA) haplotypes along an altitudinal transect in the greater white‐toothed shrew, Crocidura russula (Ehinger et al . 2002). One mtDNA haplotype (H1) rare in lowland, became widespread when approaching the altitudinal margin of the distribution. As H1 differs from the main lowland haplotype by several nonsynonymous mutations (including on ATP6), and as mitochondria play a crucial role in metabolism and thermogenesis, distribution patterns might stem from differences in the thermogenic capacity of different mtDNA haplotypes. In order to test this hypothesis, we measured the nonshivering thermogenesis (NST) associated with different mtDNA haplotypes. Sixty‐two shrews, half of which had the H1 haplotype, were acclimated in November at semioutdoor conditions and measured for NST throughout winter. Our results showed the crucial role of NST for winter survival in C. russula . The individuals that survived winter displayed a higher significant increase in NST during acclimation, associated with a significant gain in body mass, presumably from brown fat accumulation. The NST capacity (ratio of NST to basal metabolic rate) was exceptionally high for such a small species. NST was significantly affected by a gender × haplotype interaction after winter‐acclimation: females bearing the H1 haplotype displayed a better thermogenesis at the onset of the breeding season, while the reverse was true for males. Altogether, our results suggest a sexually antagonistic cyto‐nuclear selection on thermogenesis.

A Concentric Analysis of the Impact of Urbanization on the Threatened European Tree Frog in an Agricultural Landscape - JÉRÔME PELLET; ANTOINE GUISAN; NICOLAS PERRIN (Conservation Biology, 2004)
Pond‐breeding amphibians are affected by site‐specific factors and regional and landscape‐scale patterns of land use. Recent anthropogenic landscape modifications (drainage, agriculture intensification, larger road networks, and increased traffic) affect species by reducing the suitable habitat area and fragmenting remaining populations. Using a robust concentric approach based on permutation tests, we evaluated the impact of recent landscape changes on the presence of the endangered European tree frog ( Hyla arborea ) in wetlands. We analyzed the frequency of 1 traffic and 14 land‐use indices at 20 circular ranges (from 100‐m up to 2‐km radii) around 76 ponds identified in western Switzerland. Urban areas and road surfaces had a strong adverse effect on tree frog presence even at relatively great distances (from 100 m up to 1 km). When traffic measurements were considered instead of road surfaces, the effect increased, suggesting a negative impact due to a vehicle‐induced effect. Altogether, our results indicate that urbanization and traffic must be taken into account when pond creation is an option in conservation management plans, as is the case for the European tree frog in western Switzerland. We conclude that our easy‐to‐use and robust concentric method of analysis can successfully assist managers in identifying potential sites for pond creation, where probability of the presence of tree frogs is maximized.

Multiscale determinants of tree frog (Hyla arborea L.) calling ponds in western Switzerland - Jérôme Pellet; Sophie Hoehn; Nicolas Perrin (Biodiversity and Conservation, 2004)

Tests for sex‐biased dispersal using bi‐parentally inherited genetic markers - Jérôme Goudet; Nicolas Perrin; Peter Waser (Molecular Ecology, 2002)
Understanding why dispersal is sex‐biased in many taxa is still a major concern in evolutionary ecology. Dispersal tends to be male‐biased in mammals and female‐biased in birds, but counter‐examples exist and little is known about sex bias in other taxa. Obtaining accurate measures of dispersal in the field remains a problem. Here we describe and compare several methods for detecting sex‐biased dispersal using bi‐parentally inherited, codominant genetic markers. If gene flow is restricted among populations, then the genotype of an individual tells something about its origin. Provided that dispersal occurs at the juvenile stage and that sampling is carried out on adults, genotypes sampled from the dispersing sex should on average be less likely (compared to genotypes from the philopatric sex) in the population in which they were sampled. The dispersing sex should be less genetically structured and should present a larger heterozygote deficit. In this study we use computer simulations and a permutation test on four statistics to investigate the conditions under which sex‐biased dispersal can be detected. Two tests emerge as fairly powerful. We present results concerning the optimal sampling strategy (varying number of samples, individuals, loci per individual and level of polymorphism) under different amounts of dispersal for each sex. These tests for biases in dispersal are also appropriate for any attribute (e.g. size, colour, status) suspected to influence the probability of dispersal. A windows program carrying out these tests can be freely downloaded from http://www.unil.ch/izea/softwares/fstat.html

Dinucleotide microsatellite loci reveal a high selfing rate in the freshwater snail Physa acuta - Monsutti Alice; Perrin Nicolas (Molecular Ecology, 1999)